Routledge Handbook of Contemporary India - Jacobsen, Knut A. (Taylor & Francis, 2015)
ndia is the second largest country in the world with regard to population, the world's largest democracy and by far the largest country in South Asia, and one of the most diverse and pluralistic nations in the world in terms of official languages, cultures, religions and social identities. Indians have for centuries exchanged ideas with other cultures globally and some traditions have been transformed in those transnational and transcultural encounters and become successful innovations with an extraordinary global popularity. India is an emerging global power in terms of economy, but in spite of India's impressive economic growth over the last decades, some of the most serious problems of Indian society such as poverty, repression of women, inequality both in terms of living conditions and of opportunities such as access to education, employment, and the economic resources of the state persist and do not seem to go away. Now available in paperback, this Handbook contains chapters by the field's foremost scholars dealing with fundamental issues in India's current cultural and social transformation and concentrates on India as it emerged after the economic reforms and the new economic policy of the 1980s and 1990s and as it develops in the twenty-first century.